Evaluation the effectivness of Phycocyanin as antibiotic against Porphyromonas gingivalis - Yawooz Hameed Mahmood (Tikrit Journal of Pure Science)
Porphyromonas gingivalis (P. gingivalis) is considered as one of the major causes for periodontitis that eventually lead to health complications and teeth loss. In this study, crude protein extract of phycocyanin (C-PC) from Spirulina platensis that extract by precipitation and freezing/thawing methods, was assessed for its antimicrobial activity against its growth ATCC 33277, W50 wild type and  W50 (Kgp-) W50 (Rgp-) mutant type P. gingivalis strains were used to evaluate C-PC action in the bacterial inhibition at different concentrations. The results showed that there was  a decrease in ratio of the surface area for growth of bacteria has encountered in the W50 mutation strain at higher concentrations. This knowledge can be useful for the development of new oral hygienic treatments containing C-PC in the future